2022
DOI: 10.3904/kjim.2022.174
|View full text |Cite
|
Sign up to set email alerts
|

Korean Society of Nephrology 2022 recommendations on controversial issues in diagnosis and management of hyponatremia

Abstract: The Korean Society for Electrolyte and Blood Pressure Research, in collaboration with the Korean Society of Nephrology, has published a clinical practice guideline (CPG) document for hyponatremia treatment. The document is based on an extensive evidence-based review of the diagnosis, evaluation, and treatment of hyponatremia with the multidisciplinary participation of representative experts in hyponatremia with methodologist support for guideline development. This CPG consists of 12 recommendations (two for di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 95 publications
(162 reference statements)
0
4
0
Order By: Relevance
“…Sood L et al [ 41 ] even proposed the use of hypertonic saline in conjunction with desmopressin as a protocol to predict and control the rate of sodium correction. [ 42 , 43 ] In hyponatremic patients with combined craniosynostosis where salt and fluid therapy is difficult, salt corticosteroids (fludrocortisone) may be recommended to increase renal tubular sodium reabsorption; however, we are unavailable because it is not yet approved for marketing in China. Shen et al [ 44 ] reported 4 patients with refractory hyponatremia complicated with SIAD and CSWS after TBI, and a triple regimen of intravenous rehydration, hydrocortisone, and tachyphylaxis resulted in normalization of serum sodium.…”
Section: Discussionmentioning
confidence: 99%
“…Sood L et al [ 41 ] even proposed the use of hypertonic saline in conjunction with desmopressin as a protocol to predict and control the rate of sodium correction. [ 42 , 43 ] In hyponatremic patients with combined craniosynostosis where salt and fluid therapy is difficult, salt corticosteroids (fludrocortisone) may be recommended to increase renal tubular sodium reabsorption; however, we are unavailable because it is not yet approved for marketing in China. Shen et al [ 44 ] reported 4 patients with refractory hyponatremia complicated with SIAD and CSWS after TBI, and a triple regimen of intravenous rehydration, hydrocortisone, and tachyphylaxis resulted in normalization of serum sodium.…”
Section: Discussionmentioning
confidence: 99%
“… 56 Finally, the most recent guidance, published in 2022 by the South Korean Society of Nephrology , also recommends tolvaptan as second-line therapy for hyponatraemia due to SIAD. 57 …”
Section: The Position Of Tolvaptan In Guidelines For the Treatment Of...mentioning
confidence: 99%
“…With the exception of the European guidelines, 43 all other published recommendations and consensus statements 18 , 47 , 55 57 recommend tolvaptan as a second-line treatment option for SIAD in patients who do not respond to fluid restriction. Tolvaptan may also be used as a first-line agent in SIAD patients who are unlikely to respond to fluid restriction due to very limited renal excretion of solute-free water.…”
Section: Current Role Of Tolvaptan In the Management Of Siadmentioning
confidence: 99%
“…Arginine vasopressin (AVP) plays a pivotal role in maintaining fluid homeostasis in the body [6,7]. The level of circulating AVP is increased in patients with ADPKD, and the concentration of copeptin, a surrogate marker of vasopressin, is associated with disease severity [5,8].…”
Section: Introductionmentioning
confidence: 99%